Foreign direct investment in the Caribbean (UN. ECLAC/CDCC Port of SpainTT, 1995)
Aims to clarify definitions of Foreign Direct Investment (FDI), to identify the sources of information on FDI in the Caribbean, and to provide an overview of the quantum of FDI and the means used to measure it in Guyana, Jamaica, Trinidad and Tobago and the OECS.
DC